Technological aspects of managing the structural and mechanical properties of wheat bread crumb - V. Ya. Chernykh; E. V. Alekseenko; D. O. Smetanin; Kh. A. Baluyan; Yu. Yu. Pechnikova (Пищевые системы)
This work is dedicated to the study of the structural-mechanical properties of wheat bread crumb 12 hours after baking and then every 24 hours during 108 hours of storage. The basis of this investigation was the study of the starch retrogradation process, which is a transfer of the amorphous structure of starch grains into the crystalline state, which predetermines an increase in the values of the hardness parameters and hardness index. The aim of the work was investigation of an effect of the state of carbohydrate-amylase and protein-proteinase complex of wheat flour by introduction of wheat malt and dry gluten on the structural-mechanical properties of crumb of bakery products and their staling rate during storage. In this study, the authors used baker’s wheat flour of the highest grade, wheat malt, dry gluten, bread from baker’s wheat flour of the highest grade that was made using the straight dough method by the experimental laboratory baking. The authors established an effect of dosing wheat malt and dry wheat gluten on changes in the water absorption of wheat dough in the process of mixing, on its rheological properties, on the structural-mechanical properties of crumb of wheat bread made by the experimental laboratory baking as well as on the rate of its staling during storage. The optimal dosage of wheat malt was 5%, which ensured the falling number equal to 235 s. The dose of dry gluten of 3% ensured the total gluten content in dough of 31.3%, dough moisture of 43.1% and dough consistency equal to 640 FU. Simultaneous introduction of wheat malt and dry wheat gluten ensured a decrease in the hardness index of wheat bread crumb by 55% and the rate of its staling by 3.3 times.